On the N Non-Attacking Queens Problem - Bueno, Aldous Cesar Fernando (International Journal of Advanced Mathematical Sciences, 2013)
In this paper, a new version of the proof of the n-queens problem was presented. A new condition for the diagonal conflicts between the queens was added for the proof of the theorem.